2007
DOI: 10.1099/jmm.0.47239-0
|View full text |Cite
|
Sign up to set email alerts
|

One year prospective survey of Candida bloodstream infections in Scotland

Abstract: A 12 month survey of candidaemia in Scotland, UK, in which every Scottish hospital laboratory submitted all blood isolates of yeasts for identification, strain typing and susceptibility testing, provided 300 isolates from 242 patients, generating incidence data of 4.8 cases per 100 000 population per year and 5.9 cases per 100 000 acute occupied bed days; 27.9 % of cases occurred in intensive care units. More than half the patients with candidaemia had an underlying disease involving the abdomen, 78 % had an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
109
1
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 55 publications
(71 reference statements)
13
109
1
12
Order By: Relevance
“…Our susceptibility data were similar to those of other studies, and confirmed low levels of antifungal resistance among C. albicans isolates but a high level of reduced fluconazole and also reduced amphotericin B susceptibility among C. glabrata and C. krusei isolates [22,25]. There was considerable agreement between our Etest-MICs results for antifungals including those for amphotericin B, for which clinical breakpoints have not been established yet, and the EUCAST reference method [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…Our susceptibility data were similar to those of other studies, and confirmed low levels of antifungal resistance among C. albicans isolates but a high level of reduced fluconazole and also reduced amphotericin B susceptibility among C. glabrata and C. krusei isolates [22,25]. There was considerable agreement between our Etest-MICs results for antifungals including those for amphotericin B, for which clinical breakpoints have not been established yet, and the EUCAST reference method [26,27].…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of the incidence of C. dubliniensis in bloodstream infection shows that this organism is responsible for fewer than 2% of systemic Candida infections compared with over 60% by C. albicans. 6,7 Data from animal models of infection confirm that C. dubliniensis isolates are less virulent than C. albicans. In the oral-intragastric murine infection model, C. dubliniensis colonized mice less efficiently than C. albicans and were less able to establish systemic infection.…”
Section: Differential Virulence Of Candida Albicans and C Dubliniensismentioning
confidence: 92%
“…Bloodstream infections (BSI) caused by Candida species are an important cause of morbidity and mortality in hospitalised patients worldwide (Zaoutis et al 2005, Odds et al 2007, Pfaller & Diekema 2007, Hsueh & Ruan 2009. Candidaemia is generally difficult to diagnose and treat and mortality rates remain at approximately 50%, with great costs to the healthcare system (Gudlaugsson et al 2003, Colombo et al 2008, Arnold et al 2010.…”
mentioning
confidence: 99%